Mindfulness, self-efficacy, and self-regulation as predictors of psychological well-being in EFL learners - Fan, Lijuan; Cui, Feng (Frontiers in Psychology, 2024)
Introduction: Mindfulness, self-efficacy, and self-regulation play vital roles in shaping the psychological well-being of English as a Foreign Language (EFL) learners. This study investigates the interconnections among these constructs and their implications for the psychological well-being of 527 Chinese EFL learners.A cross-sectional study was conducted among Chinese EFL learners enrolled in a university in China. Participants were recruited through a non-probability convenience sampling method from English language courses. They completed validated self-report questionnaires assessing mindfulness, self-efficacy, self-regulation, and psychological wellbeing. Structural Equation Modeling (SEM) and mediation analysis were employed to explore the relationships among these constructs.The study found that mindfulness and self-efficacy independently and directly predicted psychological well-being among Chinese EFL learners. Additionally, selfregulation emerged as a significant mediator in the relationship between mindfulness and psychological well-being, suggesting that mindfulness enhances well-being indirectly through improved self-regulation skills.Discussion: These findings underscore the critical roles of mindfulness practices, selfefficacy beliefs, and self-regulation skills in promoting psychological well-being among EFL learners. The implications of this study extend to mindfulness-based interventions and programs designed. However, the study's cross-sectional design limits causal inference, and the use of self-report measures may introduce biases. Moreover, the sample's limited diversity and homogeneous demographic profile, attributed to the convenience sampling from a single university, may constrain the generalizability of the findings. Future research could adopt longitudinal designs and diverse participant samples to further elucidate these relationships and enhance the robustness of the findings.